The adaptive-evolutionary concept of information and information resources - T. F. Berestova (Библиосфера, 2018)
The article is based on the report made at the conference devoted to the 100th anniversary of the State Public Scientific Technological Library of the Siberian Branch of the Russian Academy of Sciences. The author compares different information concepts, characterizes them constructively and considers achievements of information study based on such approaches as «reflected variety», «stored choice», «sense expressed by means of communicative signs», which are regarded as obligatory procedures of information appearance/creation. The author presents own concept of information and information resources called adaptive-evolutionary one. While working out the concept, the author reveals the features of information including it into adaptive tools as well as properties formed this phenomenon. The paper shows the distinction between the concepts of «information» and «information resources» from the positions of gnoseology and onthology, in addition a functional approach to study the information phenomena is applied. Thus, based on a complex of scientific procedures the author restores speculatively the information genesis; defines its nature (generic characteristic); determines the information species properties and functions, which point it out of other facilities of human adaptation to material and social environment. Multilateral consideration of information and information resources allowed the author to make an essential definition of semantic information and information resources.